Green Synthesis of Silver Nanoparticles from Anthocyanin Extracts of Peruvian Purple Potato INIA 328—Kulli papa - Trujillo, Wiliam (2024)
In this work, AgNPs were synthesized using an anthocyanin extract from Peruvian purple potato INIA 328—Kulli papa. The anthocyanin extract was obtained through a conventional extraction with acidified ethanolic aqueous solvent. This extract acted as both a reducing and stabilizing agent for the reduction of silver ions. Optimization of synthesis parameters, including pH, reaction time, and silver nitrate (AgNO3) concentration, led to the optimal formation of AgNPs at pH 10, with a reaction time of 30 min and an AgNO3 concentration of 5 mM. Characterization techniques such as X-ray diffraction (XRD) and dynamic light scattering (DLS) revealed that the AgNPs had a crystallite size of 9.42 nm and a hydrodynamic diameter of 21.6 nm, with a zeta potential of −42.03 mV, indicating favorable colloidal stability. Fourier Transform Infrared (FTIR) analysis confirmed the presence of anthocyanin functional groups on the surface of the AgNPs, contributing to their stability. Furthermore, the bacterial activity of the AgNPs was evaluated by determining the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). For E. coli, the MIC was 0.5 mM (0.05 mg/mL) and the MBC was 4.5 mM (0.49 mg/mL). Similarly, for S. aureus, the MIC was 0.5 mM (0.05 mg/mL) and the MBC was 4.0 mM (0.43 mg/mL). These results highlight the potential benefits of AgNPs synthesized from Peruvian purple potato anthocyanin extract, both in biomedical and environmental contexts.